2010
DOI: 10.1007/s10620-010-1466-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Basis for the Medicinal Use of Psyllium Husk (Ispaghula) in Constipation and Diarrhea

Abstract: This study demonstrates that Ispaghula has a gut-stimulatory effect, mediated partially by muscarinic and 5-HT(4) receptor activation, which may complement the laxative effect of its fiber content, and a gut-inhibitory activity possibly mediated by blockade of Ca(2+) channels and activation of NO-cyclic guanosine monophosphate pathways. This may explain its medicinal use in diarrhea. It is, perhaps, also intended by nature to offset an excessive stimulant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 49 publications
(52 reference statements)
5
68
0
2
Order By: Relevance
“…To explore the possible mode of action, the spasmolytic potential of the extract was evaluated on spontaneously contracting isolated rabbit jejunum preparations (Mehmood et al, 2011;Janbaz et al, 2013;Khan et al, 2013). The increased free cytoplasmic Ca ++ activates the contractile elements in smooth muscle preparations, including rabbit jejunum (Karaki and Wiess, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the possible mode of action, the spasmolytic potential of the extract was evaluated on spontaneously contracting isolated rabbit jejunum preparations (Mehmood et al, 2011;Janbaz et al, 2013;Khan et al, 2013). The increased free cytoplasmic Ca ++ activates the contractile elements in smooth muscle preparations, including rabbit jejunum (Karaki and Wiess, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The preparations were presumed stable when three successive responses to acetylcholine were found to be identical. The isolated rabbit jejunum preparations exhibit spontaneous rhythmic contractions on which spasmolytic activity was tested directly without using any agonist (Mehmood et al, 2011). The crude extract was added to the tissue baths in cumulative manner and the obtained response was expressed as the percent change of spontaneous contractions in rabbit jejunum recorded prior to the exposure of the test material.…”
Section: Animalsmentioning
confidence: 99%
“…21 Psyllium seed husk has a laxative effect in low doses but, interestingly, has an antidiarrhoeal effect at higher doses. 22 The use of psyllium in small bowel cross-sectional imaging was first demonstrated by Vogel et al 23 in 1996, where psyllium was mixed with barium solution for CT enterography (CTE). Psyllium seed husk was later implemented in MRE in 2001 by Patak et al 19 Subsequent MRE and CTE studies provided conflicting results where two MRE studies found psyllium to have poor small bowel distension, 4,6 whereas two CTE studies argued that it provided good distension.…”
Section: Discussionmentioning
confidence: 99%
“…Each tissue was allowed to equilibrate for at least 30 min before the addition of any drug and then stabilized with repeated administration of acetylcholine (Ach, 0.3 µM) at every 3-5 min interval, until similar responses were achieved. Under similar experimental conditions, guinea-pig ileum behaved as quiescent smooth muscle preparation and is considered more useful for the assessment of spasmogenic activity (Mehmood et al, 2011), while rabbit jejunum exhibits spontaneous rhythmic contractions, allowing testing the relaxant (spasmolytic) activity directly without the use of an agonist (Gilani et al, 2008;Khan et al, 2011;Rehman et al, 2013). The relaxant responses were quantified compared to the control spontaneous beating patent of isolated jejunal preparations.…”
Section: Rabbit Jejunum and Guinea-pig Ileum Preparationmentioning
confidence: 99%